Determination of agomelatine in urine in the presence of metabolites by gas chromatography-mass spectrometry (GC-MS) - Darmograi, Natalia; Galkevych, Iryna (ScienceRise: Pharmaceutical Science, 2017)
Aim. Development and validation of the method for quantitative determination of agomelatine in urine in the presence of its metabolites using GC-MS. Methods. Chloroform was used to extract agomelatine from the urine samples, after sedimentation of uric acids by Calcium chloride. Identification and assay of the extracted agomelatine was carried out using Agilent 6890 N chromatograph with 5978 BMSD (Agilent technologies, USA) mass spectroscopy detector. Restek Rtx-5 (USA) column with 5% phenyl methyl siloxane (30m×0.25mm;0.25μm) was used for separation of the components. Carrier gas was helium. Mass detection was performed during 70 eV electronic ionization and 400 V voltages. Scanning was carried out in Scan mode within 50-550 u. Results. The developed method for agomelatine determination was validated in agomelatine linear concentration range 40-6000 ng/ml with the correlation coefficient 0.99975. The method is correct and reproducible by all parameters in the linear range of concentrations according to OECD/WHO GLP requirements, and FDA, EMA and Ministry of Health of Ukraine recommendations. Conclusion. 15 ng of agomelatine can be identified in 1 ml of urine, and 40 ng of it can be quantified by the displayed method. The total content of the detected metabolites on agomelatine concentration was approximately 35.0%. The developed method is characterized by implementation simplicity, accuracy and reproducibility, and it can be used for chemical and toxicological analysis of agomelatine